The effect of exopolysaccharides obtained from lactic acid bacteria as a prebiotic: a systematic review (Research, Society and Development, 2021)
Exopolysaccharides from lactic acid bacteria are biopolymers known for their structural diversity and because of this they have several beneficial effects on human health, and can act as immunomodulators, antioxidants, antitumors etc. It is known that exopolysaccharides also help in the balance of the intestinal microbiota, but there is still no evidence that it is due to a prebiotic effect. Therefore, this study aimed to evaluate the performance of exopolysaccharides produced by lactic acid bacteria as prebiotics through a systematic literature review. The review was carried out adopting the PRISMA strategy. Studies carried out between 2011 and 2020 were collected, using 4 different databases. The key words used were: “exopolysaccharides”, “prebiotics”, “prebiotic potential”, “prebiotic effects”, “lactic acid bacteria” and “probiotics”. A total of 7 references were analyzed regarding the prebiotic effects of EPS in general, and of these few, randomized and controlled clinical studies were carried out. Although the EPS studied have presented typical characteristics of a prebiotic, there is still a need for future studies with a better experimental design to verify these effects with greater precision, as well as to determine the appropriate duration and dosages.